Privatization and Liberalization in Labour - Managed Industries: A Welfare Analysis - Flavio Delbono (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1991)
I consider the point of view of an economic reformer aiming at improving social welfare in a currently monopolized labour-managed industry. I show that giving some tiny weight to output ti.e., consumere' surplus) in the original maximand may result in an outcome socially superior to those resulting from (partial or complete) privatization and/or liberalization.
Keywords: 330